2017
DOI: 10.3897/natureconservation.19.12659
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of different types of wood for adults of Morimus asper (Coleoptera, Cerambycidae)

Abstract: Morimus asper reproduces mainly in freshly dead wood and, as a consequence, populations are affected by modern forestry practices. The taxon M. funereus, now incorporated into the species M. asper, is protected by the Habitats Directive (Council Directive 92/43/EEC) and its monitoring has received attention in recent years. Larvae of M. asper are polyphagous, but some studies indicate that adults prefer the wood of some tree species. Freshly cut log piles, which attract adults, have been proposed as a monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
6
0
3
Order By: Relevance
“…This experiment clearly showed that adults were observed more frequently on the wood of some tree species: most individuals were observed on Juglans nigra and the least attractive tree species was Fraxinus ornus ( Figure 8A), with Quercus rubra and Carpinus betulus being intermediary (Leonarduzzi et al 2017). …”
Section: Bosco Della Fontana 2016mentioning
confidence: 97%
See 2 more Smart Citations
“…This experiment clearly showed that adults were observed more frequently on the wood of some tree species: most individuals were observed on Juglans nigra and the least attractive tree species was Fraxinus ornus ( Figure 8A), with Quercus rubra and Carpinus betulus being intermediary (Leonarduzzi et al 2017). …”
Section: Bosco Della Fontana 2016mentioning
confidence: 97%
“…a total of 13 surveys) starting at 18:00h. This research is currently being published (Leonarduzzi et al 2017).…”
Section: Parco Naturale Regionale Delle Prealpi Giulie 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…Gli adulti di M. asper sono stati cercati circa una volta a settimana dal 17.05 fino al 12.08.2016 (per un totale di 13 sessioni) partendo alle ore 18:00. I risultati di queste ricerche sono pubblicati da Leonarduzzi et al (2017).…”
Section: Parco Naturale Regionale Delle Prealpi Giulie 2016unclassified
“…Questo esperimento ha dimostrato chiaramente che gli adulti sono stati osservati più frequentemente sul legno di alcune specie di alberi: molti individui sono stati osservati su legno di J. nigra, mentre la specie meno attrattiva si è rivelata Fraxinus ornus (Figura 8A), con Q. rubra e C. betulus che mostrano un'attrattività intermedia (Leonarduzzi et al 2017). Figura 8.…”
Section: Bosco Della Fontana 2016unclassified